The Effectiveness of Linear Algebra E-Modules with the Integration of Islamic Values and Muhammadiyah Principles on Student Learning Outcomes: Efektivitas E-Modul Aljabar Linier dengan Integrasi Nilai-Nilai Al Islam Kemuhammadiyahan terhadap Hasil Belajar Mahasiswa - Ariyanti, Novia (Indonesian Journal of Innovation Studies, 2025)
General background: The rapid advancement of digital technology has significantly transformed education, particularly in the development of innovative learning media such as electronic modules (E-modules). Specific background: In higher education, especially within Muhammadiyah universities, learning is not only directed at mastering academic content but also at fostering Islamic character through the integration of Al Islam and Kemuhammadiyahan (AIK) values. This integration is highly relevant in abstract subjects like Linear Algebra, where students often face challenges in conceptual understanding. Knowledge gap: While prior studies have demonstrated the benefits of E-modules for enhancing mathematical comprehension and motivation, limited research has specifically investigated the combined effect of E-modules and AIK value integration on both learning outcomes and character formation. Aims: This study aims to analyze the effectiveness of a Linear Algebra E-module integrated with AIK values in improving student learning outcomes and strengthening Islamic character. Results: Using a quasi-experimental one-group pretest-posttest design, findings revealed an increase in average student scores from 55.8 (pre-test) to 81.5 (post-test), with an N-Gain of 0.59, categorized as moderate-to-high effectiveness. Novelty: This research uniquely bridges technological innovation in digital learning with the pedagogical mission of Muhammadiyah education, offering a holistic approach that combines cognitive mastery with spiritual and character development. Implications: The study provides theoretical contributions to educational technology by demonstrating the value of integrating religious-based frameworks into digital learning tools, while practically offering a model for educators to design character-based digital media that enhances both academic achievement and moral values. Highlights: Integration of AIK values into digital learning enhances both academic and character development. E-Module implementation shows significant improvement in student performance (N-Gain = 0.59). Offers a novel model combining technology-based learning with Islamic pedagogical principles. Keywords: E-Module, Linear Algebra, Al Islam Kemuhammadiyahan, Learning Outcomes, Character Education